Tinjauan terhadap rekabentuk dan persekitaran ruang kerja staf sokongan di Universiti Malaysia Sarawak - Faizah, Abdul Ghani (Universiti Malaysia Sarawak, 2005)
This study aims to observe the design and the environment of the workplace among the support staff in UNIMAS. The observation is done in order to find the factors ofthe design and environment ofthe workplace that can affect satisfaction, safety and health among the workers. In this study the problem of the design and workspace environment were obtained through interviews with respondents who are also the support staff of the UNIMAS. Some of the problems that have been identified are uncomfortable of the small workplace, sound distraction and health problem associated with the usage of the computer and workstation seat. This research is conducted using the library research method that is based on the literature review. The problems that have been identified were analyzed to discuss and some suggestions were made in order to improve the level of comfort, health and safety of the support staff based on the past research Therefore it is hoped that the findings from this research would help the management of UNIMAS to improve the design and environment of the workplace in order to fulfill the comfort and satisfaction of workers apart of their safety and health. This can be done by organize the more detail research based on the principle of ergonomic especially that could be applied in the future campus.